2013
DOI: 10.1165/rcmb.2012-0377oc
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Metalloproteinases–3 Moderates the Proinflammatory Status of Macrophages

Abstract: Tissue inhibitor of metalloproteinases-3 (TIMP-3) has emerged as a key mediator of inflammation. Recently, we reported that the resolution of inflammation is impaired in Timp3 2/2 mice after bleomycininduced lung injury. Here, we demonstrate that after LPS instillation (another model of acute lung injury), Timp32/2 mice demonstrate enhanced and persistent neutrophilia, increased numbers of infiltrated macrophages, and delayed weight gain, compared with wild-type (WT) mice. Because macrophages possess broad imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…For example, in mice lacking TIMP3, fibrosis is enhanced following bleomycin-induced injury, suggesting that the presence of TIMP3 would actually restrict ECM deposition [58]. While the mechanism leading to this fibrosis remains to be determined, Timp3 −/− mice have impaired resolution of inflammation following lung injury, which could contribute to the enhanced fibrotic response [58,59].…”
Section: Indirect Regulation Of Ecm Turnover By Timp3mentioning
confidence: 99%
“…For example, in mice lacking TIMP3, fibrosis is enhanced following bleomycin-induced injury, suggesting that the presence of TIMP3 would actually restrict ECM deposition [58]. While the mechanism leading to this fibrosis remains to be determined, Timp3 −/− mice have impaired resolution of inflammation following lung injury, which could contribute to the enhanced fibrotic response [58,59].…”
Section: Indirect Regulation Of Ecm Turnover By Timp3mentioning
confidence: 99%
“…For example, MMP12 and MMP28, both macrophage products, either promote or restrict macrophage influx into lung (10, 11), and MMP8 promotes M2 polarization (12). In addition, we reported that MMP28 and TIMP3, an MMP inhibitor, moderate M1 activation of macrophages in models of lung infection and fibrosis (13, 14). As their name implies, MMPs are thought to degrade extracellular matrix proteins, a function that is indeed performed by some members (1517).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TIMP3 deficiency prolongs bleomycin-induced lung inflammation with alveolar neutrophilia and prevents resolution of inflammation (53). In LPS-induced lung inflammation, lack of TIMP-3 was associated with increased macrophage polarization into the inflammatory M1 phenotype (52). Although TIMP3 seems to attenuate proinflammatory events in the lung, it is not clear to what extent this is mediated by the inhibition of ADAM17 or other metalloproteinases (Table 2).…”
Section: Adam17mentioning
confidence: 99%